2021
DOI: 10.1016/j.heliyon.2021.e07100
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported use of and access to personal protective equipment among healthcare workers during the COVID-19 outbreak in Nigeria

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…However, studies conducted during the pandemic also revealed problems with supply of personal protective equipment. Oladele et al reported that 55.4% of health workers had problems with finding personal protective equipment [46] while Murat et al reported that 36.1% of nurses had the same problem [38]. 55.3% of nurses in this study reported problems with accessing personal protective equipment which is in line with the literature.…”
Section: Discussionsupporting
confidence: 88%
“…However, studies conducted during the pandemic also revealed problems with supply of personal protective equipment. Oladele et al reported that 55.4% of health workers had problems with finding personal protective equipment [46] while Murat et al reported that 36.1% of nurses had the same problem [38]. 55.3% of nurses in this study reported problems with accessing personal protective equipment which is in line with the literature.…”
Section: Discussionsupporting
confidence: 88%
“…The use of appropriate PPE by HCW in this study was recorded among less than a half, similar to another study in Nigeria which reported 44.9%, [26] but much less than 84.4% reported from India. [25] Poor epidemic preparedness and the widespread report of PPE shortages at the pandemic's start contributed immensely to the lack of PPE during the pandemic.…”
Section: Discussionsupporting
confidence: 87%
“…A crosssectional survey of HCW in Nigeria had reported the facility type and gender as significant predictors of PPE use. [26] An Ethiopian study also reported IPC training and access to IPC guidelines as significantly associated with good COVID-19 behaviour. In contrast, another study from Uganda reported age and educational qualification of HCW as significantly associated with safety practices, but these variables were not significant in the present study.…”
Section: Annals Of Health Research Volume 8 Issue No 1 2022__________...mentioning
confidence: 96%
“…In this way, the social working activities and collaborative networks of VHVs can portray how the local community in northeastern Thailand is responding to the COVID-19 pandemic. Numerous scholars have paid attention to various topics on multiple effects and impacts of the pandemic ( Golar et al 2020 ; Ripon et al 2020 ; Rume & Islam 2020 ; Abbas et al 2021 ; Pongutta et al 2021 ) and certain effective strategies and policies governments and private sectors cope with Covid-19 ( Ejeh et al, 2020 ; Yazdanirad et al 2021 ; Oladele et al 2021 ). As such, however, none of them have explored the important roles of community’s voluntary networks, who facilitate the implementations of healthcare policy in the countryside areas.…”
Section: Introductionmentioning
confidence: 99%